Relative validity effects with either one or two more valid cues in Pavlovian and instrumental conditioning. - Murphy, R; Baker, A; Fouquet, N (2001)
Two experiments investigated the relative validity effect with either 1 or 2 continuously reinforced cues in Wistar rats using appetitive Pavlovian and instrumental preparations. Discrimination training involved 3 compound cues containing a common element (1AX: 1BX: 2CX). In the first true-discrimination group (TD-1), CX was followed by food, but AX and BX were not. In the second true-discrimination group (TD-2), AX and BX but not CX were followed by food. In the third, pseudodiscrimination group (PD), food followed 50% of each compound. Compared with the PD group, there were lower levels of responding to X in Groups TD-1 and TD-2, which did not differ. That is, both TD treatments showed equivalent relative validity effects. There was evidence for a relative validity effect on the context. The Rescorla-Wagner model incorrectly predicts a smaller relative validity effect after the TD-2 than the TD-1 treatment. Comparator theory predicts these results.